Bias Konfirmasi terhadap Perilaku Berbohong - Fiqhiyatun Naja; Nanik Kholifah (Ilmu Psikologi Universitas Yudharta Pasuruan, 2020)
The spread of fake news in Indonesia is now increasingly widespread, especially through social media, many negative impacts have been caused from the spread of fake information. Fake information can defame the reputation of others, cruel slander, fighting between groups, and disrupt national disintegration and even disrupt national security stability. Confirmation bias is one of the reasons why someone conducts or disseminates fake information, where individuals tend to only seek and receive information that is in accordance with their thoughts and ignores different opinions that might be true facts. This study aims to measure the effect of confirmation bias on lying behavior that is prevalent around us. The sample in this study was the millennial generation of social media users who are members of the PMII Pasuruan organization of 80 members, the samples were taken by purposive sampling technique. Data collection used a lying behavior scale and a confirmation bias scale compiled by the researchers using Likert answer method. The data were then analyzed using One Predictor Linear Regression Analysis. The results of data analysis resulted r value of 0.102228 with a significance value of 0.286. This shows that there is no significant correlation between confirmation bias and lying behavior.